REM sleep behaviour disorder differentiates pure autonomic failure from multiple system atrophy with autonomic failure. Issue 5 (1st May 1998) - Plazzi, Giuseppe; Cortelli, Pietro; Montagna, Pasquale; De Monte, Alessandro; Corsini, Raffaella; Contin, Manuela; Provini, Federica; Pierangeli, Giulia; Lugaresi, Elio
Abstract : Ten patients with primary autonomic failure, followed up in a prospective clinical and laboratory study, were finally diagnosed as pure autonomic failure or multiple system atrophy with autonomic failure. Polysomnographic studies were performed in all patients. Whereas all four patients with multiple system atrophy complained of sleep related episodes suggesting REM sleep behaviour disorder (RBD) confirmed by polysomnography, RBD remained absent in the remaining six patients with pure autonomic failure. The data indicate that RBD is an important clinical feature, often heralding multiple system atrophy, but which is absent throughout the course of pure autonomic failure; its recognition can thus be useful in the prognostic evaluation of early primary autonomic failure syndromes.